The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1029/2008gl035285
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric HULIS enhance pollutant degradation by promoting the dark Fenton reaction

Abstract: [1] Humic-like substances (HULIS) in the atmosphere are ubiquitous macromolecular substances that comprise a major fraction of the organic component of atmospheric aerosols. In this study we report that HULIS extracted from collected wood burning and urban pollution atmospheric particles enhance aqueous phase oxidation of model organic contaminants (pyrene and phenol), by promoting the dark Fenton reaction under atmospherically relevant conditions. The paucity of radical sources at night makes this reaction, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Because HULIS encompasses a complex and varying suite of molecules in different locations, it is difficult to predict the impact of HULIS photochemistry on Barrow snow grains. However, past work has identified a number of the (photo)chemical pathways involving HULIS in ice and surface waters, including water assisted cooperative sorption of organic compounds onto HULIS, changing their structure [ Taraniuk et al , 2009], contribution of atmospheric HULIS to (nighttime) oxidation of organic pollutants in cloud water via the dark (and photo‐) Fenton reaction [ Moonshine et al , 2008], oxidative photodegradation of HULIS and formation of aryl aldehydes [ Cowen and Al‐Abadleh , 2009], light‐induced ozone depletion by HULIS [ D ' Anna et al , 2009], and its possibly essential role in HONO production from photochemical reactions of NO 3 − in snowpacks [ Beine et al , 2008]. Finally, unknown chromophores (i.e., not NO 3 − , NO 2 − , H 2 O 2 , or HULIS) are responsible for approximately half of sunlight absorption by Barrow snows, implying that there is a significant amount of uncharacterized photochemistry that is occurring in these samples, with possible implications for snowpack cycling of carbon, nitrogen, halogens, and oxidants.…”
Section: Resultsmentioning
confidence: 99%
“…Because HULIS encompasses a complex and varying suite of molecules in different locations, it is difficult to predict the impact of HULIS photochemistry on Barrow snow grains. However, past work has identified a number of the (photo)chemical pathways involving HULIS in ice and surface waters, including water assisted cooperative sorption of organic compounds onto HULIS, changing their structure [ Taraniuk et al , 2009], contribution of atmospheric HULIS to (nighttime) oxidation of organic pollutants in cloud water via the dark (and photo‐) Fenton reaction [ Moonshine et al , 2008], oxidative photodegradation of HULIS and formation of aryl aldehydes [ Cowen and Al‐Abadleh , 2009], light‐induced ozone depletion by HULIS [ D ' Anna et al , 2009], and its possibly essential role in HONO production from photochemical reactions of NO 3 − in snowpacks [ Beine et al , 2008]. Finally, unknown chromophores (i.e., not NO 3 − , NO 2 − , H 2 O 2 , or HULIS) are responsible for approximately half of sunlight absorption by Barrow snows, implying that there is a significant amount of uncharacterized photochemistry that is occurring in these samples, with possible implications for snowpack cycling of carbon, nitrogen, halogens, and oxidants.…”
Section: Resultsmentioning
confidence: 99%
“…HULIS is characterized to contain a high density of quinoid units and carboxylate groups. As a result, HULIS may enhance the aqueous phase oxidation of organic pollutants in the atmosphere via its ability to promote the Fenton reaction (Moonshine, Rudich, Katsman, & Graber, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have shown that HULIS can be important in Published by Copernicus Publications on behalf of the European Geosciences Union. P. Lin et al: Humic-like substances in fresh emissions of rice straw burning the troposphere in issues such as hygroscopic growth and cloud condensation nuclei formation of aerosols (Dinar et al, 2006;Gysel et al, 2004), light extinction (Hoffer et al, 2006;Lukacs et al, 2007), atmospheric chemistry processes such as aqueous-phase oxidation of organic pollutants (Moonshine et al, 2008) and ozone depletion on aerosol surfaces (D'Anna et al, 2009).…”
Section: Introductionmentioning
confidence: 99%